Preliminary clinical experience with a thermal balloon endometrial ablation method for menorrhagia - Yang, Qi-Sheng (Journal of Innovative Studies, 2020)
The TB endometrial therapeutic apparatus for menorrhagia is used to coagulate, necrosis, exfoliate, and fibrosis endometrial tissue proteins with heat energy.Treatment of menorrhagia TB endometrial therapeutic apparatus stripping: using heat to make endometrial tissue protein coagulation, necrosis, peeling, fibrosis. TB endometrial therapeutic apparatus is composed of two parts, one is a hot bulb catheter, the other is a controller to monitor and control the temperature, pressure, and treatment time in the bulb. The first function is the pneumatic system, which can detect the air pressure of the heating system and provide positive and negative pressure for the instrument; the second is the heating system, which can heat the treatment fluid as a heat source and measure the instantaneous temperature in the ball and is limited to 173 ℃; the third is the control system, which can control the heating temperature and treatment time of the instrument within 128 seconds and the pressure value so that the treatment fluid can make 14 cycles between the catheter and the balloon. Before treatment, acute infection and organic lesions were excluded by routine examination. After that, the guide rod ball was inserted into the uterine cavity to touch the uterine bottom, and the scale of the guide rod was checked to see whether it was consistent with the depth of the uterine cavity. Then, a 5% glucose solution was slowly injected into the bulb through the interface, so that the pressure in the uterine cavity gradually increased to 170-190 mm Hg and kept stable. The heating system was started, and the temperature of the solution in the ball increased to 87 ℃. After treatment, when the temperature in the ball drops below 60℃, take out the liquid in the ball and take out the guide rod. During the treatment, the controller continuously monitors the temperature, pressure, and time in the ball. The patients were discharged from the hospital 2 days after the operation. The patients were followed up 1,2,3,6,12,18 months after the treatment.